Abraham Lincoln - Oberle, Lora Polack (North Mankato : Bridgestone Books, 2002)
This book is a dedication to the 16th President and commander-in-chief of the United States of America: Abraham Lincoln. To show how respected and influential President Lincoln was, before, during, and after his reign and tenure as President, this book traces a genealogical line through his life, death, and legacy.To begin, this book explores Lincoln's childhood and some of the experiences and events that may have had a hand in him becoming one of the most famous American presidents.Moving forward, this book includes chapters that each touch on and highlight topics such as Lincoln's entrance into the political arena, memorable moments from the Lincoln presidency, and the controversy of his death.The final chapter includes and explores the legacy Abraham Lincoln left behind, both for his family and for the American people, not to mention people worldwide who remain to be influenced by his words and actions.Ultimately, this book shows and explores the reasons why President Abraham Lincoln is remembered to be one of the greatest presidents of the United States of America, and why his death was such a shock, trauma, and tragedy for those who truly believed in his greatness.
R
800
R
Keywords: Presidents -- United States -- Biography -- Juvenile literature; Presidents